Determinant Factors to Improve Quality Education in The Faculty of Manufacturing Technology General Achmad Yani University - Patra, Oviyan; Tuti Leni Suaningsih; Zaenal Muttaqien; Hendy Suryana (Fakultas Ekonomi dan Bisnis, Telkom University., 2025)
To make UNJANI into an outstanding university requires individuals who can think and act quickly, withstand difficulties, and succeed in competition. To become an excellent university, it must meet the criteria for achieving the Main Performance Indicators set by the Directorate of Higher Education. UNJANI has consistently strived to improve its compensation structure, as it is believed to enhance company performance. The Faculty of Manufacturing Technology implements policies for teaching staff through a compensation structure to improve the quality of education, including educational and teaching performance, research performance, and community service performance. This study aims to explore the influence of compensation structure on employee performance and the improvement of educational quality at the Faculty of Manufacturing Technology, Universitas Jenderal Achmad Yani (UNJANI). This research uses a quantitative method with a survey approach. Data were collected through questionnaires distributed to faculty staff, supplemented with supporting data and interviews to gain a deeper understanding. The data analysis utilized descriptive and inferential statistical techniques to examine the relationships between the variables in the study. The results show that the compensation structure has a significant effect on employee performance, which in turn positively impacts the quality of education. These findings provide practical implications for university management in designing and implementing effective compensation policies to enhance employee performance and educational quality. As a recommendation from this study, management should conduct regular reviews of the compensation structure and develop training programs to improve employee performance.